Multilateral treaties deposited with the Secretary-General - United Nations ([s.l] : United Nations, 2005)
This CD-ROM contains information on treaty actions relating to multi lateral treaties deposited with the Secretary-General
Text (Treaties).
System requirements: Microsoft windows 95, 98, ME, NT, 2000 or XP, I ntel Pentium processor, 32 MB of RAM (64 MB recommended), 150 MB of ava ilable hard-disk space and CD-ROM drive.
Requires Adobe Reader 6.0 or higher.
The CD contain its contents in English and French.
Keywords: Treaties